Characterisation and comparative genomics of three new Varanus-associated Borrelia spp. from Indonesia and Australia - Alexander William Gofton; Angel Popa-Baez; Ai Takano; Kari Soennichsen; Michelle Michie; Makenna Short; Supriyono Supriyono; Jack Pascoe; Sue Cusbert; Robert Mulley (Parasites & Vectors, 2023)
Abstract Background Borrelia are important disease-causing tick- and louse-borne spirochaetes than can infect a wide variety of vertebrates, including humans and reptiles. Reptile-associated (REP) Borrelia, once considered a peculiarity, are now recognised as a distinct and important evolutionary lineage, and are increasingly being discovered worldwide in association with novel hosts. Numerous novel Borrelia spp. associated with monitor lizards (Varanus spp.) have been recently identified throughout the Indo-Pacific region; however, there is a lack of genomic data on these Borrelia. Methods We used metagenomic techniques to sequence almost complete genomes of novel Borrelia spp. from Varanus varius and Varanus giganteus from Australia, and used long- and short-read technologies to sequence the complete genomes of two strains of a novel Borrelia sp. previously isolated from ticks infesting Varanus salvator from Indonesia. We investigated intra- and interspecies genomic diversity, including plasmid diversity and relatedness, among Varanus-associated Borrelia and other available REP Borrelia and, based on 712 whole genome orthologues, produced the most complete phylogenetic analysis, to the best of our knowledge, of REP Borrelia to date. Results The genomic architecture of Varanus-associated Borrelia spp. is similar to that of Borrelia spp. that cause relapsing fever (RF), and includes a highly conserved megaplasmid and numerous smaller linear and circular plasmids that lack structural consistency between species. Analysis of PF32 and PF57/62 plasmid partitioning genes indicated that REP Borrelia plasmids fall into at least six distinct plasmid families, some of which are related to previously defined Borrelia plasmid families, whereas the others appear to be unique. REP Borrelia contain immunogenic variable major proteins that are homologous to those found in Borrelia spp. that cause RF, although they are limited in copy number and variability and have low sequence identities to RF variable major proteins. Phylogenetic analyses based on single marker genes and 712 single copy orthologs also definitively demonstrated the monophyly of REP Borrelia as a unique lineage. Conclusions In this work we present four new genomes from three novel Borrelia, and thus double the number of REP Borrelia genomes publicly available. The genomic characterisation of these Borrelia clearly demonstrates their distinctiveness as species, and we propose the names Borrelia salvatorii, ‘Candidatus Borrelia undatumii’, and ‘Candidatus Borrelia rubricentralis’ for them. Graphical Abstract